Model Predict-Observe-Explain Meningkatkan Hasil Belajar Siswa - Afanti, Rizqi Wahyu; Nurfahrudianto, Aan; Sahari, Sutrisno (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
This study aims to determine student learning outcomes before the aapplication of the Predict-Observe-Explain (POE) learning model supported by video tutorials on the material of heat and its transfer < 75, to determine stundet learning outcomes after the application of the Predict-Observe-Explain (POE) learning model supported by video tutorials on the material of heat and its transfer â‰¥ 75, to determine ehether there is n effect of the application of Predict-Observe-Explain (POE) learning model supported by video tutorial on the material of heat and its transfer on student learning outcomes. The research methodology used is quantitative whit a One Grub Pretetst-Posttest research design. The population in this study were 30 students of grade V SDN Mlancu 2. The sample used in this study was a total sampling of 30 students. The insrtuments used were pretest and posttest. The pretest was used before treatment was given, the posttest was used after treatment was given. Research results (1) student learning otcomes before the application of the Predict-Observe-Explain model supported by video tutorials on the material on heat and its transfer < 75 (2) student learning otcomes after the application of the Predict-Observe-Explain model supported by video tutorials on the material on heat and its transfer â‰¥ 75 (3) there is an influence of the application of the Predict-Observe-Explain learning model supported by video tutorials on the material of heat and its transfer on student learning outcomes.